2023
DOI: 10.1111/apa.16652
|View full text |Cite
|
Sign up to set email alerts
|

The safety of COVID‐19 vaccination in immunocompromised children and young adults with immune‐mediated inflammatory disease

Abstract: Aim:To assess safety of COVID-19 vaccination in paediatric patients with immunemediated inflammatory disease (IMID).Methods: Subjects of 5-21 years of age with IMID who received at least one COVID-19 vaccine completed electronic surveys after each vaccine to assess side effects within 1 week of vaccination, current medications and COVID-19 testing after vaccination.Charts were reviewed for COVID-19 polymerase chain reaction and IgG response to SARS-CoV-2 spike protein results and for disease flare during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…53,54) In previous pediatric cohort studies, most immunocompromised children and young adults had an appropriate humoral and cellular immune response, side effects were mild, and disease flare rates were low following COVID-19 vaccination. [55][56][57] This supports the need for a continuous emphasis on COVID-19 vaccination among the immunocompromised pediatric population, consistent with recommendations. 55,58,59) We also suggest that further studies examine the relationship between immunocompromised status and the risk of long COVID in children.…”
Section: Discussionsupporting
confidence: 72%
“…53,54) In previous pediatric cohort studies, most immunocompromised children and young adults had an appropriate humoral and cellular immune response, side effects were mild, and disease flare rates were low following COVID-19 vaccination. [55][56][57] This supports the need for a continuous emphasis on COVID-19 vaccination among the immunocompromised pediatric population, consistent with recommendations. 55,58,59) We also suggest that further studies examine the relationship between immunocompromised status and the risk of long COVID in children.…”
Section: Discussionsupporting
confidence: 72%
“…Systemic AEs did not differ between patients and controls while lower rate of local symptoms was found post-vaccination in children with IBD. This is in line with previous studies in which decreased rate of post-vaccination AEs have been reported in pediatric patients with immune-mediated inflammatory disease taking immunosuppressive medication as compared to healthy subjects ( 19 ). In this cohort, only 2 IBD flares were detected 2-6 weeks after the second dose of BNT162b2 mRNA vaccination, while in 3 cases, disease activity was lower post-vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…In this cohort, only 2 IBD flares were detected 2-6 weeks after the second dose of BNT162b2 mRNA vaccination, while in 3 cases, disease activity was lower post-vaccination. These results support previous data ( 19 22 ) and provide reassurance that BNT162b2 mRNA vaccination in paediatric IBD patients is safe and well-tolerated. Our report is the first to support the safety of mRNA vaccination in a paediatric cohort with detailed laboratory data including ACE2 activity, inflammatory parameters and thrombin generation pre- and post-vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…This might result in a reduction of the self-imposed social distancing measures, which have been shown to increase depression and anxiety rates, as well as impaired social development [41][42][43]. Taken together with the reported low risk profile of the BTN162b2 vaccination in immunocompromised patients [44], the data underscores the beneficial effect of vaccination in this vulnerable population.…”
Section: Discussionmentioning
confidence: 73%